Antiphospholipid syndrome after streptococcal toxic shock syndrome later diagnosed as Behcet's disease. Issue 3 (26th April 2023) - Kourti, Afroditi; Mentesidou, Lida; Michalopoulou, Aikaterini; Maritsi, Despoina; Bachou, Theodora
Abstract : Streptococcal toxic shock syndrome is a severe complication of group A streptococci. The production of antiphospholipid antibodies has been associated with streptococcal infections and with autoimmune diseases. Furthermore, streptococcal infections could be a trigger of Behcet's disease. We report a case of a boy who presented antiphospholipid syndrome after streptococcal toxic shock syndrome later he was diagnosed with Behcet's disease.